Analisis Proses Pembelajaran Dalam Jaringan di Masa Pandemi Covid-19 - Antonius Bere (MUKADIMAH: Jurnal Pendidikan, Sejarah, dan Ilmu-ilmu Sosial, 2022)
The Covid-19 pandemic had an impact on various sectors of the world be it economic, social, political. The central government up to the local level provides policies to dissolve all educational institutions. This is done to break the chain of spread of the Covid-19 virus. The study also aims to find out how obstacles and expectations are during online learning in this pandemic period. This research uses literature research methods, where this research in the collection of information and data using a variety of materials and materials in the library. The obstacles during online learning are inadequate internet networks, limited ownership of gadgets and difficulty achieving learning goals.